Tunisia's Global Integration : Second Generation of Reforms to Boost Growth and Employment - World Bank (Washington, DC, 2012)
This report addresses the following issues: Chapter one takes stock of the integration policies implemented since the early 1970s and assessed their impact on foreign direct investments (FDI), exports and employment. Chapter two looks at today's major challenges in the manufacturing sector and the specific policies needed to address them. Chapter three assesses the entry, business, and trade restrictions in Tunisia's key backbone services sectors (telecommunication, banking, air transport, accounting, auditing, and legal services) using a well-focused regulatory questionnaire. The restrictiveness indices calculated from the regulatory questionnaire are then used to benchmark Tunisia against Organisation for Economic Co-operation and Development (OECD) and some emerging economies and to simulate the impact of various liberalization options on the price of services and the economy via a multi-region general equilibrium model. Finally, chapter four examines the prospect for increasing exports and off shoring of a large number of services for which Tunisia has demonstrated a strong capacity for export in recent years. The significant increase in real incomes in Tunisia is the result of solid gross domestic product (GDP) growth since the mid-1960s (5 percent a year), low inflation and the demographic transition, faster than in neighboring countries. In 1996-2007, economic growth has exhibited greater resilience to moderate exogenous shocks, thanks to prudent macroeconomic management public debt declined from 62.4 percent in 2001 to 50.9 percent of GDP in 2007 thanks to pro-active debt management. The resulting decline in the debt service since 2005 combined with steady GDP growth allowed the government to 'protect' capital expenditures and key social spending within the context of low but structural fiscal deficit. While the current account remained in deficit over the last 10 years, foreign exchange reserves increased steadily thanks to increasing FDI inflows. In 2007, international reserves increased by US$ 1 billion to US$ 7.8 billion, representing 4.6 months of imports of goods and services.